A cross-sectional study on internet addiction among medical students - S., Cynthia Subhaprada; P., Kalyani (International Journal Of Community Medicine And Public Health, 2017)
Background: Proliferation of the internet has provided better opportunities for communication, information and social interaction. The excessive undisciplined use by individuals has led to the emergence of the concept of internet addiction. Psychological and environmental factors in the lives of college students may leave them disproportionately vulnerable to Internet addiction. The main objective of this study was to measure prevalence of internet addiction and the usage pattern among undergraduate medical students. Methods: The present cross-sectional study was carried out among 95 undergraduate students of II MBBS, selected by simple random sampling, in Kurnool Medical College, Kurnool, Andhra Pradesh, from January to February, 2016. A 20 item Young’s Internet Addiction test which is a Likert scale based interview schedule was used to measure the prevalence of internet addiction. Data was entered in MS Excel 2007 and analyzed. Chisquare test was applied and p value <0.05 considered significant. Results: Among the 95 study subjects, 62.2% were males and 37.8% were females. Males were more addicted to internet than females. The prevalence of internet addiction among the study subjects in the present study was 52.63% mild, 24.21% moderate, while 23.16% students reported normal internet usage. It was found that severity of internet addiction is inversely proportional to academic performance. Conclusions: Internet addiction is a growing health problem among medical students, hence necessary preventive and therapeutic interventions are vital to promote healthy and safe usage of Internet.